Flexible polymeric patch based nanotherapeutics against non-cancer therapy - Zhu, Houjuan (2022)
Flexible polymeric patches find widespread applications in biomedicine because of their biological and tunable features including excellent patient compliance, superior biocompatibility and biodegradation, as well as high loading capability and permeability of drug. Such polymeric patches are classified into microneedles (MNs), hydrogel, microcapsule, microsphere and fiber depending on the formed morphology. The combination of nanomaterials with polymeric patches allows for improved advantages of increased curative efficacy and lowered systemic toxicity, promoting on-demand and regulated drug administration, thus providing the great potential to their clinic translation. In this review, the category of flexible polymeric patches that are utilized to integrate with nanomaterials is briefly presented and their advantages in bioapplications are further discussed. The applications of nanomaterials embedded polymeric patches in non-cancerous diseases were also systematically reviewed, including diabetes therapy, wound healing, dermatological disease therapy, bone regeneration, cardiac repair, hair repair, obesity therapy and some immune disease therapy. Alternatively, the limitations, latest challenges and future perspectives of such biomedical therapeutic devices are addressed.